For this response, I will assume that abc = -27 instead of 27, as it is impossible for 3 negative numbers to multiply to a positive number

The minimum value is 64

Expanding (1-a)(1-b)(1-c), we have −abc+ab+ac+bc−a−b−c+1

Thus, to find what the minimum value for the desired expression is, we have to calculate the minimum of -a-b-c, and the minimum of ab+ac+bc.

Since a, b, and c are negative, we cannot use the AM-GM inequality for 3 variables on it, but after multiplying each of the variables by -1, making them positive, we have \(\frac{-a-b-c}{3}≥ \sqrt[3]{-abc}\), simplifying to \(-(a+b+c)≥9\), so the minimum value of -(a+b+c) is 9.

Since a, b, c are negative, ab, ca, and bc must all be positive, hence allowing for an easy AM-GM application. \(\frac{ab+ac+bc}{3}≥\sqrt[3]{abc^2}\), simplifying to \(ab+ac+bc≥ 27\). Both -(a+b+c) and ab+ac+bc reach the minimum value when the equality condition of the AM-GM inequality is met, namely, when -a=-b=-c, or when a=b=c, and when ab=ac=bc. Both of these simplify to a=b=c. Since abc=-27, a=b=c=-3. Thus, the minimum value of −abc+ab+ac+bc−a−b−c+1 occurs when a=b=c=-3, rendering the minimum value of (1-a)(1-b)(1-c) as 64, as you assumed.

Hopefully this answered your question, have a great day!